Improving Semangat Belajar Siswa Mata Pelajaran Aqidah Akhlak Melalui Pendekatan Variasi Pembelajaran Di MTs. Subulus Salam - Halid, Ahmad; Aman Siddiq Al Ghafir, Abu; Ali Rosyidi, Imron (MADINAH, 2019)
It is very important for teachers to apply a variation approach to learning with the consideration that each student has a different character every day and a different capacity in capturing the subject matter presented by the teacher in class. This study aims to find out how individual, group and educative learning approaches increase the spirit of learning Aqidah Akhlak at MTs Subulus Salam which is located at MTs Subulus Salam, Dusun Rowotengu, Pucuan Village, Semboro District, Jember Regency. While the method used is descriptive qualitative with data collection techniques through observation, documentation and interviews. The results of the study show that the variation approach can increase the spirit of learning, because there is a combination of teaching methods that are fun for students, and the success of teachers with a variation approach can build good communication between educators and students